A Study on the Role of Leadership: Exploring the Role of Leaders in Managing Diversity and Creating Sustainable Enterprises (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The creation and maintenance of sustainable enterprises requires an understanding of the role of management in addressing employees ' personal outcomes. Happiness is everybody's mutual aim, and most other stuff can imply that aim. Organizations are driven by dynamic world economies to think beyond their goods and the bottom line to go beyond only staff motivation and to provide a committed workforce. Companies are shifting their framework owing to globalization and operating in a wider arena. Most of these organisations used to think of capital simply as securities, assets, savings, or resources of some type. In a transforming world, the evolving position of leaders in recruiting, maintaining and engaging with a diverse population gives rise to criteria for interactive leadership competency. This paper suggests that managing diversity requires business leaders to take a diversity management approach that is not only sensitive to race and ethnic differences, but also to the background and values of all people at work.